RELEVANSI METODE PENDIDIKAN RASULULLAH DALAM KONTEKS PENDIDIKAN MODERN - Suriadi Suriadi (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
Students are less interesting in religious lessons. This is not only experienced by elementary school students until senior high school students, but also felt by Islamic elementary school students until Islamic senior high school students. this has an impact on the religious quality of society that declines compared to the previous era.Especially compared to the time of the Prophet `. Many factors influence it. One of them is suspected due to the fact that the teaching method is less interesting. To offer a solution to this factor, it is worth a look back the ways of the Prophet in educating his friends. Furthermore, the methods are contextualized in modern education. It can not be separated from the adaptation and modification of these methods. In this paper will be presented a track record of educational methods of the Prophet` and that relenvance with modern educational methods.